Secure Cryptographic Mechanisms for Safeguarding Citizen Communications in the Presence of Tyranny. Issue 2 (2013) - Saab, Soulaf; Itani, Wassim; Kayssi, Ayman; Chehab, Ali; Ghali, Cesar
No abstract available